Prevalencia de la enfermedad periodontal y su relación en pacientes con o sin problemas oclusales que acuden a la Universidad de las Américas. - Cabezas López, Mercy Eva (2017)
Periodontal diseases are currently one of the main global problems of oral health, since it causes severe damage to the protection and support of the tooth tissues. The objective of the present study is to determine the prevalence of periodontal disease and their relationship in patients who present or no occlusal problems. The study was conducted in the Clinic of the University of the Americas, in 60 patients periodontal, being a cross-sectional study, exploratory and descriptive. It valued the following variables: type of periodontitis (chronic and aggressive) and type of dental occlusion, based on two types of classifications, classification according to Angle - molar relation, taking to the first molars definitive or key Robins - relationship canine based on the canines. Getting the following results: chronic periodontitis 90 percent, aggressive periodontitis 10 percent. In the type of dental occlusion: classification according to Angle - molar relationship 68.3 percent, and key Robins - relationship canine 31.7 percent, demonstrating that the majority of patients do present the first molars definitive. Within the chronic periodontitis was found that: the class one (molar - canine) presents a 27.8 percent, class two (molar - canine) a 59.3 percent, and class three (molar - canine) a 12.9 percent, while in aggressive periodontitis class one (molar - canine) presents a 16.6 percent, class two (molar - canine) a 83.4 percent, and class three (molar - canine) a 0 percent. In general it was observed that the prevailing class two with a 61.7 percent, followed by the class one with 26.7 percent and finally the class three with 11.7 percent. It was concluded that the prevalence of periodontal diseases related to malocclusions dental is high, however it was also shown the presence of periodontal disease in class one dental.